ГРЕЛИН И ОГРАНИЧИТЕЛЬНОЕ ПИЩЕВОЕ ПОВЕДЕНИЕ У ДЕВОЧЕК-ПОДРОСТКОВ, СТРАДАЮЩИХ ОЖИРЕНИЕМ - Евдокимова, Нина Викторовна; Похлебкина, Алевтина Алексеевна; Мильнер, Евгения Борисовна; Гурина, Ольга Петровна; Блинов, Александр Евгеньевич; Варламова, Ольга Николаевна; Шогирадзе, Лаура Джумбертовна; Новикова, Валерия Павловна (FORCIPE, 2022)